2008
DOI: 10.1016/j.cell.2008.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Transcription-Independent Loss of Nucleosomes over a Large Chromatin Domain at Hsp70 Loci

Abstract: SUMMARY To efficiently transcribe genes, RNA Polymerase II (Pol II) must overcome the barrier imposed by nucleosomes and higher order chromatin structure. Many genes, including Drosophila melanogaster Hsp70, undergo changes in chromatin structure upon activation. To characterize these changes, we mapped the nucleosome landscape of Hsp70 following an instantaneous heat shock at high spatial and unprecedented temporal resolution. Surprisingly, we find an initial disruption of nucleosomes across the entire gene w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
338
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(373 citation statements)
references
References 68 publications
(95 reference statements)
25
338
2
4
Order By: Relevance
“…But nucleosomes can also be removed from gene bodies independently of transcription. Previous studies of the Hsp70 locus in Drosophila have shown that heat-shock induces rapid and transcription-independent loss of gene-body nucleosomes (Petesch and Lis 2008). Finally, it is possible that the 14°C temperature increase itself perturbs nucleosomes.…”
Section: Nucleosome Fragility Increases Throughout Heat-shock Genes Umentioning
confidence: 99%
“…But nucleosomes can also be removed from gene bodies independently of transcription. Previous studies of the Hsp70 locus in Drosophila have shown that heat-shock induces rapid and transcription-independent loss of gene-body nucleosomes (Petesch and Lis 2008). Finally, it is possible that the 14°C temperature increase itself perturbs nucleosomes.…”
Section: Nucleosome Fragility Increases Throughout Heat-shock Genes Umentioning
confidence: 99%
“…While some ARTDs modify substrates by transferring iteratively multiple ADP-ribose units resulting in poly-ADP-ribosylation (PARylation), most ARTDs mono-ADP-ribosylate (MARylate) their substrates (Kleine et al, 2008). ARTDs function in DNA damage repair (Malanga and Althaus, 2005;Nicolae et al, 2014Nicolae et al, , 2015, the unfolded protein response (Jwa and Chang, 2012), apoptosis Koh et al, 2005), heat shock (Petesch and Lis, 2008), cellular signaling (Feijs et al, 2013a;, cell division (Chang et al, 2004(Chang et al, , 2005(Chang et al, , 2009Ha et al, 2012), as well as transcription and chromatin regulation Schreiber et al, 2006). PARylating ARTDs (pARTDs; ARTD1-6), most prominently ARTD1, have been the focus of cancer related research during the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…PARP1-ECFP (red) and PARP Δ300 -EYFP (green) protein localization was detected by autofluorescence of ECFP and EYFP. binding of PARP and its enzymatic activation were shown to be critical for Pol2 polymerase-dependent transcription within the Hsp70 gene (7,27). Here, we compared distribution of PARP1-ECFP and PARP Δ300 -EYFP proteins along the hsp70 locus in parp C03256 mutants.…”
Section: Parp δ300 Protein Is Enriched In Regions Of Euchromatin and Ismentioning
confidence: 99%
“…PARP1 enzymatic activity has also been shown to be required for normal assembly of higher order chromatin structures and for transcriptional activation (6). Moreover, it has been shown that PARP1 regulates the transcription of these genes by inducing chromatin loosening at targeted genetic loci (6,7). Finally, PARP1 establishes silent chromatin domains and represses retrotransposable elements (8).…”
mentioning
confidence: 99%